ETIKA KOMUNIKASI DALAM KOMENTAR NETIZEN DI YOUTUBE: Studi Etnografi Virtual pada Konten Live Sidang Ijazah Palsu Berlanjut Rocky Gerung Jadi Saksi Ahli di Youtube Refly Harun dan Konten Refly Harun Mencium Bau Intimidasi Soal Gugatan Penundaan Pemilu 2024 di YoutubetvOneNews - Sapari, Yusuf; Suhara, Rizki Budhi; Riaeni, Ida; Suherman, Suherman (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2024)
Advances in technology and the internet have not only given rise to new media but have become a human need to interact and socialize, one of which is communication technology innovation in the form of social media. With social media that can be accessed by the wider community, people in villages and cities also get the same information about education, technology, knowledge and so on. The development of the use of social media as a means of communication is increasingly rapid after the internet can be accessed via cell phones, even now people can access it anytime, anywhere using a smartphone or the term gadget has emerged which makes it easier for people to access it anywhere and anytime without any time limits. Good communication ethics in consuming social media and in accordance with Islamic teachings are not to use harsh words, pornography, or "SAR" issues and do not post false articles or statuses, which will later cause conflict, and do not post articles or statuses that are not true. or images that are copyrighted. There are many theories that explain the ethics of using social media, namely being able to use correct language, be polite, not insult people and not engage in body shaming. The aim of this research is to determine communication ethics in netizen comments on the live content of the fake diploma trial continuing with Rocky Gerung becoming an expert witness on Refly Harun's Youtube and Refly Harun's content smelling of intimidation regarding the lawsuit for postponing the 2024 Election on Youtube tvOneNews. The theory used is communication ethics with Cyber ​​Media Analysis (AMS). The method in this research is a qualitative virtual ethnographic approach. The results and conclusions of this research are the essence of communication ethics in netizen comments on YouTube, namely as a process in conveying messages from the communicator to the communicant with intent and meaning. This means that in conveying the message there needs to be ethics or rules. This is so that the communication message to be conveyed has the same meaning for both the communicator and the communicant. YouTube Refly Harun and tvOneNews, namely the existence of video content which of course has informative benefits and goodness. It also contains basic elements, namely faith, sharia, broadcasting and good morals. Keywords :Communication Ethics, Virtual Ethnography, Cyber ​​Media Analysis, Netizens, Youtube